2018
DOI: 10.1111/cob.12261
|View full text |Cite
|
Sign up to set email alerts
|

‘Say no’: a feasibility trial of a brief intervention to reduce instances of indulgent energy‐intake episodes

Abstract: The aim of this study is to examine the feasibility of a brief intervention to reduce instances of indulgent energy intake. Forty-five participants with a body mass index (BMI) ≥25 kg m- were randomized to one of three groups for 8 weeks. The control group was asked to complete a questionnaire every 4 days, the self-monitoring group was given the same instructions but also asked to 'say no' to indulgences. The self-monitoring and feedback group was asked to do the same but in addition to send a photograph or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…The difference in weight of 1 kg between the groups at follow up is similar to the result of another study where participants made between 9 and 13 small changes to their indulgence intake each week (Madigan et al, 2018). Whilst a modest difference in weight was recorded between the groups at follow-up in the current study, this should be considered in light of research showing that the average adult gains 0.5-1.0 kg each year (Hutfless et al, 2013;Williamson 1993), which can lead to the development of overweight and obesity over time and that even small changes in weight can have a significant impact.…”
Section: Discussionsupporting
confidence: 83%
“…The difference in weight of 1 kg between the groups at follow up is similar to the result of another study where participants made between 9 and 13 small changes to their indulgence intake each week (Madigan et al, 2018). Whilst a modest difference in weight was recorded between the groups at follow-up in the current study, this should be considered in light of research showing that the average adult gains 0.5-1.0 kg each year (Hutfless et al, 2013;Williamson 1993), which can lead to the development of overweight and obesity over time and that even small changes in weight can have a significant impact.…”
Section: Discussionsupporting
confidence: 83%
“…Details relating to the recruitment of participants into the ‘Say No’ trial have been reported elsewhere [ 14 ]. To summarise, 45 participants were recruited, and the inclusion criteria were as follows: aged ≥18 years, with a BMI ≥ 25 kg/m 2 , and participants that were motivated to reduce the number of indulgent foods and beverages they consumed.…”
Section: Methodsmentioning
confidence: 99%
“…However, many of these are high in saturated fats, sugars, salt, and/or alcohol and are therefore described as “energy dense nutrient poor” [ 10 ]. Elsewhere in the literature, researchers/practitioners refer to these types of foods as snacks [ 11 , 12 , 13 ] or as indulgences [ 14 ]. Snacks may not always be high in fat/sugar or be energy-dense, and indulgences may mean different things to different people [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation